Metaphors of Postmodernism in Neo-Victorian Fiction: “The Trial of Elizabeth Cree” by Peter Ackroyd and “The Decorator” by Boris Akunin - Baratova, Olga A.; Shamina, Vera B.; Apenko, Elena M. (Journal of History Culture and Art Research, 2017)
One of the features that characterizes postmodern fiction is an intense interest in the past, and especially so – in Victorian period, chiefly in its sensational aspects. Therefore we witness a revival of Victorian crime novel and this tendency can be traced not only in recent English literature, but in other literatures as well, Russian in particular. This gave birth to the term “neo-Victorian novel”, referring to the pieces, which recreate the atmosphere of the period, introduce a lot of intertextual allusions and references to the well-known Victorian novels and exploit most popular subjects of the 19th century literature. However as we will argue in this essay the authors often use these plots as implicit metaphors of postmodern art as such. It will be demonstrated on the example of two Neo-Victorian novels – “The Trial of Elizabeth Cree” by Peter Ackroyd (1995) and “The Decorator” by Boris Akunin; for the latter Ackroyd’s novel can be also regarded as one of the precedent texts. Both novels give their versions of the story of Jack the Ripper but what is more important in our case – employ akin plot structures, images and artistic devices, which in fact become metaphoric actualization of postmodern techniques.